1997
DOI: 10.1002/art.1780401222
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal dysfunction in scleroderma. Relationship with disease subsets

Abstract: Objective. To investigate the relationship between esophageal function and the extent of disease in a nonselected group of scleroderma patients, and to study gastric and small bowel motility in a group of scleroderma patients with more severe clinical manifestations.Methods. Esophageal function in 125 scleroderma patients was investigated by radiologic, endoscopic, manometric, and pH-metric techniques. Ten patients also underwent gastrointestinal (GI) manometric recording, both during fasting and after a stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
8

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 49 publications
(27 reference statements)
3
37
0
8
Order By: Relevance
“…Response to treatment was arbitrarily de®ned as a total score of < 3, while a score of > 3 was considered as treatment failure (or relapse). 9 Oesophageal manometry was carried out according to a previously described technique, 9,10 with the resting LES pressure measured by station pull-through and oesophageal body activity evaluated in response to at least 10 wet swallows (5 mL of water) administered 30 s apart.…”
Section: Methodsmentioning
confidence: 99%
“…Response to treatment was arbitrarily de®ned as a total score of < 3, while a score of > 3 was considered as treatment failure (or relapse). 9 Oesophageal manometry was carried out according to a previously described technique, 9,10 with the resting LES pressure measured by station pull-through and oesophageal body activity evaluated in response to at least 10 wet swallows (5 mL of water) administered 30 s apart.…”
Section: Methodsmentioning
confidence: 99%
“…On histological examination, smooth muscle atrophy and fibrosis causing motor activity abnormalities in two-thirds of the distal esophagus are often determined (4). Motility studies have shown that the amplitude of peristaltic contractions decreases or that there is no peristaltic contraction in this region (5)(6)(7). Abnormal peristalsis and decreased lower esophageal sphincter (LES) pressure reduce acid clearance and prolong the contact of acid with the mucosa (8).…”
Section: Systemic Sclerosismentioning
confidence: 99%
“…La compromissione della peristalsi mostrava nella nostra casistica la distribuzione caratteristica della SSc, coinvolgendo il terzo inferiore del viscere in quasi tutti i pazienti e quello medio in circa la metà, risparmiando invece il tratto superiore. La prevalenza della compromissione dello svuotamento esofageo nella nostra casistica (68% dei pazienti) è in linea con i maggiori studi della letteratura che hanno impiegato la scintigrafia (14,19,22) e si avvicina a quelle riportate dai lavori che hanno utilizzato la manometria (23,24). L'alterato svuotamento esofageo non è risultato correlato con la durata di malattia, molto protratta e simile nei gruppi di pazienti con diversa forma clinica di SSc della nostra casistica.…”
Section: Discussioneunclassified
“…La compromissione della peristalsi del viscere, sia in toto sia del suo terzo inferiore, è risultata significativamente meno frequente e di minore entità nei pazienti con forma cutanea limitata rispetto a quelli con forme diffusa e intermedia di SSc. Questo dato è in accordo con la maggior parte dei lavori della letteratura (23)(24)(25)(26) e mette in discussione il vecchio assioma che identificava nell'esofagopatia uno degli elementi caratterizzanti la forma cutanea acrolocalizzata di SSc, la cosiddetta CREST. In effetti soltanto il 50% dei nostri pazienti con forma limitata di SSc presentava una peristalsi esofagea alterata.…”
Section: Discussioneunclassified